2005
DOI: 10.1080/10511482.2005.9521544
|View full text |Cite
|
Sign up to set email alerts
|

Does housing wealth contribute to or temper the widening wealth gap in America?

Abstract: Does housing help to increase or temper the widening gap in the distribution of wealth? Paradoxically, it may do both. Housing wealth is still the cornerstone of household wealth, and homeowners hold almost all of the nation's wealth. The uneven distribution of household net wealth is worsening, even though housing helped homeowners increase net wealth during the last recession. Because housing wealth is more balanced than other types of wealth and home equity is more important to low-income and minority house… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 5 publications
1
18
0
Order By: Relevance
“…However, homeownership may not pay off as well as other potential investments. Low-income households often overinvest in homeownership and sell at a real loss (Beracha & Johnson 2012, Di 2005, Herbert & Belsky 2008). The rise of predatory lending and the devastating effects of foreclosure on families calls into question whether average wealth gains justify these inequalities in risk and outcomes (Pattillo 2013).…”
Section: Housing Effects On Socioeconomic Statusmentioning
confidence: 99%
“…However, homeownership may not pay off as well as other potential investments. Low-income households often overinvest in homeownership and sell at a real loss (Beracha & Johnson 2012, Di 2005, Herbert & Belsky 2008). The rise of predatory lending and the devastating effects of foreclosure on families calls into question whether average wealth gains justify these inequalities in risk and outcomes (Pattillo 2013).…”
Section: Housing Effects On Socioeconomic Statusmentioning
confidence: 99%
“…32,33 Finally, housing is one of the most important sources of wealth for low-income households in the United States, 26,33,34 and to the extent that wealth is a determinant of health status 35,36 housing loss would be expected to have substantial effects on health. In addition to harming the health of the individual undergoing foreclosure, these community-level mechanisms can be expected to have a detrimental effect on the health of community members who are not themselves undergoing foreclosure.…”
mentioning
confidence: 99%
“…To buttress the argument for expanding homeownership to minimize wealth disparities, policy makers pointed to the significant role of housing equity in the transmission of intergenerational wealth (Di, 2005; Harkness & Newman, 2003; Shapiro & Wolff, 2001). A 2005 study of homeownership and wealth demonstrated the greater importance of homeownership wealth for African Americans and for lower‐income people (Di, 2005). While for all groups homeowners accumulated more wealth than did renters, the ratio was higher for African‐American homeowners compared to renters (37:1) than for White homeowners and renters (25:1).…”
Section: Social Reproduction and Homeownershipmentioning
confidence: 99%